MEREDAM KONFLIK PLURALISME AGAMA DENGAN SPIRITUALITAS AL-QUR’AN - Habibah, Nuraini (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
Plurality is inevitable. There is no single reality in this life. Humans are destined by God to have tribes and nations with different physical characteristics, thoughts, cultures, religions, ideologies, and traditions. These differences often cause tension and prolonged conflict and often result in loss of life. Of all the differences, religion is assumed to be the one that most often triggers conflict, because religion is the most fundamental and sensitive thing for every human being. Religious conflicts, both internal and inter-religious, can occur due to several factors such as differences in beliefs, differences in interpretation, religious fanaticism, and intervention from outside interests. It is important to provide an understanding to religious people that religious differences must be addressed with an awareness of religious pluralism. Religious pluralism is understood as an understanding that recognizes the existence of other religions outside of one's religion and respects them to practice the teachings of one's religion. Religious pluralism does not justify other religions, let alone consider them the same. Religious pluralism views that each religious person still holds a strong commitment to their respective religions. One effort that can be done to reduce religious conflict is to build awareness of religious spirituality in each religious adherent. Being religious is not just a formulation of rituals of worship, in fact the practice of rituals of worship is a form of presentation of a person's religious spirituality, which then the devout person must present himself in the form of a human being with noble morals. So religious spirituality must be implemented in the form of obedience to worship which then produces humans with noble morals. Thus, religious people whose level of religious spirituality is good should respect religious differences and dislike religious conflicts.